Heavy and Light Mineral Association of Late Quaternary Permafrost Deposits in Northeastern Siberia - Schirrmeister, L.; Wetterich, S.; Schwamborn, G.; Matthes, H.; Grosse, G.; Klimova, I.; Kunitsky, V. V.; Siegert, C. (Frontiers in Earth Science, 2022)
We studied heavy and light mineral associations from two grain-size fractions (63–125 μm, 125–250 µm) from 18 permafrost sites in the northern Siberian Arctic in order to differentiate local versus regional source areas of permafrost aggradation on the late Quaternary time scale. The stratigraphic context of the studied profiles spans about 200 ka covering the Marine Isotope Stage (MIS) 7 to MIS 1. Heavy and light mineral grains are mostly angular, subangular or slightly rounded in the studied permafrost sediments. Only grains from sediments with significantly longer transport distances show higher degrees of rounding. Differences in the varying heavy and light mineral associations represent varying sediment sources, frost weathering processes, transport mechanisms, and post-sedimentary soil formation processes of the deposits of distinct cryostratigraphic units. We summarized the results of 1141 microscopic mineral analyses of 486 samples in mean values for the respective cryostratigraphic units. We compared the mineral associations of all 18 sites along the Laptev Sea coast, in the Lena Delta, and on the New Siberian Archipelago to each other and used analysis of variance and cluster analysis to characterize the differences and similarities among mineral associations. The mineral associations of distinct cryostratigraphic units within several studied profiles differ significantly, while others do not. Significant differences between sites as well as between single cryostratigraphic units at an individual site exist in mineral associations, heavy mineral contents, and mineral coefficients. Thus, each study site shows individual, location-specific mineral association. The mineral records originate from multiple locations covering a large spatial range and show that ratios of heavy and light mineral loads remained rather stable over time, including glacial and interglacial periods. This suggests mostly local sediment sources and highlights the importance of sediment reworking under periglacial regimes through time, including for example the formation of MIS 1 thermokarst and thermo-erosional deposits based on remobilized MIS 3 and 2 Yedoma Ice Complex deposits. Based on the diverse mineralogical results our study supports the viewpoint that Yedoma Ice Complex deposits are mainly results of local and polygenetic formations (including local aeolian relocation) superimposed by cryogenic weathering and varying climate conditions rather than exclusive long distance aeolian transport of loess, which would have highly homogenized the deposits across large regions.